Berberine inhibits the development of endometrial cancer through circ_ZNF608/miR-377-3p/COX2 axis. (30th September 2022) - Liang, Huan; Liu, Yi; Fu, Lian; Li, Ling; Gong, Nianjin
Abstract: Objective: Endometrial carcinoma (EC) is a common malignant tumour in women. Berberin (BBR) is an alkaloid with anti-tumour activity, and circular RNA (circRNAs) has been extensively studied in cancers. However, whether BBR regulates the development of EC by regulating circular RNA zinc finger protein 608 (ZNF608) is unknown. Methods: Different concentrations of BBR were used to treat endometrial cancer cells. A quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to assess the expression of circ_ZNF608, microRNA-377-3p (miR-377-3p) and cyclooxygenase 2 (COX2). The expression of COX2 protein was detected by western blot. The effect of circ_ZNF608 in BBR-treated EC cells was verified by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, thymidine analog 5-ethynyl-2'-deoxyuridine (EdU) assay, colony formation assay, transwell, and flow cytometry. The effect of BBR and circ_ZNF608 on tumour growth was evaluated by xenograft tumour model in vivo . Results: Berberine can inhibit the proliferation and metastasis of EC cells and promote apoptosis, which is related to the concentration. Circ_ZNF608 and COX2 were abnormally increased, while the levels of miR-377-3p were reversed in EC tissues and cells. Overexpression of circ_ZNF608 can restore the inhibitory effect of BBR on EC cells. In addition, circ_ZNF608 restored the inhibitory effect of BBR on EC cells by inhibiting the expression of miR-377-3p. Similarly, MiR-377-3p/COX2 can regulate the tumour progression of EC under BBR. Finally, BBR can inhibit the growth of endometrial carcinoma in vivo . Conclusion: BBR was found to inhibit EC via the circ_ZNF608/miR-377-3p/COX2 axis, which is helpful in endometrial carcinoma.